المشترك اللفظي وأثره في التّكَوثُر الدّلالي بين الإثبات والإنكار - بن مخلوف, ربيع (جامعة الوادي - university of Eloued, 2022)
يتناول هذا البحث المشترك اللفظي كظاهرة لغويّة ضاربة العمق في التراث اللغويّ العربيّ القديم، ومنفتحة على مستجدّات البحث اللغويّ الحديث، وإذ يستدعي المشترك اللفظي علائق اللفظ بمعانيه، وأثرها في تنامي معاني الألفاظ وتكوثرها الدّلالي، فإنَّه يُعدُّ واحدًا من المباحث التي أُوليت باهتمام بالغٍ من اللغويين القدامى والمحدثين على حدّ سواء، لما له من أثرٍ في استقصاء المعاني والدّلالات من ألفاظها، حتى غدت العلاقات الدلالية محور اهتمام اللغويين المحدثين فيما كان يطلق عليها اسم الظواهر اللغوية لدى علماء اللغة الأقدمين، ليتبلور المصطلح بشكل علمي دقيق وواضح المعالم ضمن دائرة الدراسات اللغوية، وقد انقسم الباحثون إزاء المشترك اللفظي إلى فريقين: يرى أحدهما بوقوعه في اللغة وأثره البيِّن في التنامي الدّلالي للألفاظ، وفريقٌ آخر يُنكر ذلك البَتّة ويَعدُّه من خوارم تكامل اللغة العربية في ثراء ألفاظها ومؤدّاها، ليخلص البحث في ختامه إلى جدوى أهميّة المشترك اللفظي وفحوى تمظهراته الـمُسهِمة في الزّخم اللفظي والدّلالي في اللغة العربية. Abstract: This research deals with the verbal joint as a linguistic phenomenon of great depth in the ancient Arabic linguistic heritage, and open to the developments of modern linguistic research, since the verbal joint calls for the relationships of the word with its meanings, and its impact on the growth of the words meanings and their semantic development, it is considered one of the topics that were given great attention by ancient and modern linguists alike, because of its impact on the meanings exploring and connotations of its terms, until semantic relations became the focus of attention for modern linguists in what was called linguistic phenomena among older linguists, so that accurate and well-defined scientific terms crystallize within the circle of linguistic studies that bring together these linguistic phenomena, primarily the verbal joint. With respect to the joint verbal, the researchers are divided into two groups: one of them sees its falling in the language and its clear impact on the semantic development of the words, and the other group denies that at all and considers it one of the flaws of the Arabic language integration under the richness of its words and its substance, At the end of the research, it concludes with the usefulness of the importance of the verbal joint and the content of his manifestations contributing to the verbal and semantic momentum in Arabic.
The verbal joint and its impact on the semantic development between affirmation and denia
مقال
Keywords: المشترك اللفظي، التكوثر الدّلالي، العلاقات الدلالية، الظواهر اللغوية، الإثبات، الإنكار; Verbal joint, semantic multiplication, semantic relations, linguistic phenomena, affirmation, denial.